Energetika bytových domů - Krampera, Jan; Jan Krampera (České vysoké učení technické v Praze, 2021)
V této práci je vytvořený ucelený souhrn energetiky rodinných a bytových domů. V práci jsou podrobně popsány jednotlivé druhy zdrojů energie a jednotlivé druhy tepelných izolací pro rodinné a bytové domy. Další část práce se zabývá problematikou komunitní energetiky, jejím současným rozvojem v České republice a ve světě a její závislostí na legislativě a podpoře dané země. V závěru práce jsou jednotlivé varianty zdrojů energie a tepelných izolací pro rodinné a bytové domy vzájemně porovnány z pohledu ročních nákladů na vytápění a z pohledu kritérií ekonomické efektivnosti. Ekonomicky nejpříznivější varianty jsou dále srovnávány s variantou využití technologie řízeného větrání s rekuperací.

In this thesis, a comprehensive summary of family and apartment houses energetics is created. The thesis describes the various types of energy sources and various types of thermal insulation for family and apartment buildings. The next part of the thesis addresses the issues of community energetics, its current development in the Czech Republic and in the world and its dependence on legislation and support of the country. At the end of the thesis, the individual variants of energy sources and thermal insulation for family and apartment houses are compared with each other in terms of annual heating costs and in terms of economic efficiency criteria. The most economically favorable variants are further compared with the variant of using controlled ventilation technology with recuperation.
Energetics of apartment buildings
Keywords: Zdroj energie; tepelná izolace; komunitní energetika; řízené větrání s rekuperací; potřeba tepla na vytápění; kritéria ekonomické efektivnosti; Energy source; thermal insulation; community energy; controlled ventilation with recuperation; heat demand for heating; criteria of economic efficiency